Bicorniphontodes (Copepoda: Harpacticoida: Laophontodinae Lang, 1944): a new genus with description of a new species from the Napoleon Reef, Gulf of Aqaba, Red Sea, Egypt - George, Kai Horst; George, Kai Horst; Glatzel, Thomas; Schröder, Katharina (Zootaxa, 2019)
Findings of a new representative of the Laophontodinae Lang, 1944 (Copepoda, Harpacticoida) from the Napoleon Reef (Gulf of Aqaba, Red Sea, Egypt) provided new insights into the systematics of the type genus Laophontodes T. Scott, 1894. Bicorniphontodes clarae gen. et sp. nov., which is described in the present contribution, shares exclusively six derived characters with Laophontodes bicornis A. Scott, 1896, L. horstgeorgei George & Gheerardyn, 2015, and partly with L. hamatus (Thomson, 1883), and L. ornatus Krishnaswamy, 1957: (1) cephalothorax medio-laterally with triangular extensions and (2) postero-laterally with paired cuticular processes, (3) free body somites except telson dorsally with hyaline frills ending in rounded lappets, (4) furcal setae I and II displaced subapically, (5) antennar allobasis lacking abexopodal seta on endopodal half, (6) outer spines of the last segment of swimming legs 2 and 3 unipinnate and comb-like, with the pinnae being extremely long and set widely apart. Thus, the named species are excluded from Laophontodes and united together with B. clarae gen. et sp. nov. in Bicorniphontodes gen. nov. as Bicorniphontodes bicornis comb. nov., B. hamatus comb. nov., B. horstgeorgei comb. nov., and B. ornatus comb. nov.. Beside the description of B. clarae gen. et sp. nov., a detailed phylogenetic discussion regarding the systematic relationships of the named species and the justification of the erection of Bicorniphontodes gen. nov. is given, including its distribution in the world’s oceans. A key to species is also provided.